Pharmacokinetic boosting to enable a once-daily reduced dose of tofacitinib in patients with rheumatoid arthritis and psoriatic arthritis (the PRACTICAL study). (December 2022) - van der Togt, Céleste J.T.; Verhoef, Lise M.; van den Bemt, Bart J.F.; den Broeder, Nathan; ter Heine, Rob; den Broeder, Alfons A.
Background: Tofacitinib is a Janus Kinase (JAK) inhibitor used for the treatment of rheumatoid arthritis (RA) and psoriatic arthritis (PsA), dosed as 5 mg twice daily (BID). It is primarily metabolized by the cytochrome P-3A (CYP3A) enzyme, and therefore, the manufacturer recommends to halve the dose when using CYP3A-inhibiting co-medication. Combining half-dose tofacitinib with a registered CYP3A inhibitor (cobicistat) could reduce costs and improve patient experience. Objectives: Primary: bioequivalence of tofacitinib 5 mg combined with cobicistat once daily (QD; intervention) to tofacitinib 5 mg BID (control). Secondary: safety, patient preference (7-point Likert scale at study end) and predicted differences in disease activity (DAS28-CRP and probability of ACR20 response) using a validated exposure-response model. Design: Open-label, cross-over pharmacokinetic study. Methods: We included patients with RA or PsA, treated with tofacitinib 5 mg BID for ⩾14 days without co-medication affected by CYP3A inhibition. Pharmacokinetic sampling was performed at baseline and after 2–6 weeks of intervention treatment. Bioequivalence was defined as 90% CI of the average tofacitinib concentration (Cavg, ss ; intervention to control) falling between 80% and 125%, assessed by non-linear mixed-effects modelling. Results: Between 16 September 2019 and 15 January 2021, 30 patients were included, of whom 25 completed both PK measurements. The tofacitinib Cavg, ss was 85% (90% CI: 75–96%). No serious adverse events occurred. Patient preference was 56% for intervention versus 18% for control. No relevant differences in median predicted disease activity were found (DAS28-CRP: 0.03, 95% CI: −0.16 to 0.22; ACR20: −0.01, −0.07 to 0.05). Conclusion: Due to slightly lower tofacitinib concentrations during intervention treatment, pharmacokinetic bioequivalence could not formally be established. However, pharmacokinetic boosting may be an attractive strategy for cost reduction of tofacitinib because of its safety, similar predicted pharmacodynamics and patient preference. Registration: This study was registered on 29 May 2019 in the Netherlands Trial Register (register number: NL7766).